Modelling the trade-off between fire and grazing in a tropical savanna landscape, northern Australia - Liedloff, Adam C.; Coughenour, Michael B.; Ludwig, John A.; Dyer, Rodd (Environment international, 2001)
As savannas are widespread across northern Australia and provide northern rangelands, the sustainable use of this landscape is crucial. Both fire and grazing are known to influence the tree–grass character of tropical savannas. Frequent fires open up the tree layer and change the ground layer from perennials to that dominated by annuals. Annual species in turn produce copious quantities of highly flammable fuel that perpetuates frequent, hot fires. Grazing reduces fuel loads because livestock consumes fuel–forage. This trade-off between fire and grazing was modelled using a spatially explicit, process-orientated model (SAVANNA) and field data from fire experiments performed in the Victoria River District of northern Australia. Results of simulating fire (over 40 years) with minimal or no grazing pressure revealed a reduction in the shrub and woody plants, a reduction in grasses, and no influence on the tree structure given mild fires. While mature trees were resistant to fire, immature trees, which are more likely associated with the shrub layer, were removed by fire. The overall tree density may be reduced with continual burning over longer time periods because of increasing susceptibility of old trees to fire and the lack of recruitment. Increases in stocking rates created additional forage demands until the majority of the fuel load was consumed, thus effectively suppressing fire and reverting to the grazing and suppressed fire scenario where trees and shrubs established.